2015
DOI: 10.18051/univmed.2015.v34.121-128
|View full text |Cite
|
Sign up to set email alerts
|

Albendazole increases serum retinol concentration in primary schoolchildren with low serum retinol

Abstract: BACKGROUNDSoil-transmitted helminth (STH) infection is still a health problem in Indonesia. Vitamin A deficiency (VAD) is often found together with STH. The effect of the deworming program on the vitamin A status of primary school children is unknown. The objective of this study was to evaluate the effect of albendazole on serum retinol concentrations in primary school children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, there was very little known about the effects of vitamin A supplementation on Ascaris lumbricoides infections. We investigated the effects of vitamin A supplementations (mega-dose; 200,000 IU) on the Ascaris lumbricoides reinfection [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was very little known about the effects of vitamin A supplementation on Ascaris lumbricoides infections. We investigated the effects of vitamin A supplementations (mega-dose; 200,000 IU) on the Ascaris lumbricoides reinfection [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Its expected result after deworming accompanied by giving vitamin A could decrease prevalence and intensi-ty of helminthiasis [9]. A study in Canada reported that giving vitamin A in albendazole decreased ascariasis [10,11]. The interaction between albendazole and vitamin A was still unclear.…”
Section: Introductionmentioning
confidence: 99%